PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA TOKO BEN’S LAUNDRY MEDAN - Ginting, Samuel T.U.A; Siahaan, Lasma Melinda (Politeknik Negeri Lhokseumawe, 2024)
Abstract: Medan is a developing city with high economic growth, which continues to increase every year, where the economic growth rate in the Medan City area in 2022 is 4.71% (www.bps.go.id), which of course can cause several problems, so that currently The company in each of its business management also pays attention to improving service quality and prices in all areas in accordance with community needs which can generate customer loyalty, including the need for cloth washing or laundry.The aim of this research is to determine the level of customer loyalty from the influence of service quality and prices at the Ben's Laundry Shop in Medan. Then this research can find out which variable is more dominant, where the Independent variable (X) is: Service Quality (X1), Price (X2) and the dependent variable (Y) is Customer Loyalty.This research is based on quantitative descriptive analysis, measuring each variable with numbers, data analysis, statistics, and using the SPSS software application, as well as assessment using intervals, the average score of variables X1, X2, and Y from respondents' assessments (Sugiyono, 2017). and the value of the multiple regression coefficient that the conclusions X1 and Then X jointly influences Y through the multiple coefficient of determination test, while the remaining variables influence it. Looking for variable X that is more dominant over variable Y through the partial coefficient test (r). The publication of the research output is a research journal that has an Online Journal System (OJS), so researchers are interested in the research title, namely